2003
DOI: 10.1016/s0021-9517(03)00239-2
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure liquid phase hydroconversion of heptane/nonane mixtures on Pt/H-Y zeolite catalyst

Abstract: The competitive hydroconversion of heptane and nonane molecules in their mixture was studied in a continuous flow, fixed-bed reactor filled with Pt/HY zeolite catalyst. Liquid-phase reaction conditions were established at reaction temperatures of 230, 250, and 270 • C by pressurizing the reactor at 100 bar. Hydrogen was supplied in an absorbed state with the liquid hydrocarbon feed. Under these liquidphase reaction conditions, the apparent reaction rates of heptane and nonane were almost identical. In a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…These observations are further supported by Denayer et al, 21 in which it was shown that the reaction in the liquid phase was essentially unaffected by the differences in adsorption, in contrast to that observed in similar experiments in the gas phase. The assumption of equal molar loadings for all hydrocarbons is inherent in the LH approach.…”
Section: Reaction In the Liquid Phasesupporting
confidence: 71%
See 2 more Smart Citations
“…These observations are further supported by Denayer et al, 21 in which it was shown that the reaction in the liquid phase was essentially unaffected by the differences in adsorption, in contrast to that observed in similar experiments in the gas phase. The assumption of equal molar loadings for all hydrocarbons is inherent in the LH approach.…”
Section: Reaction In the Liquid Phasesupporting
confidence: 71%
“…21,30,31,34 Thus, the competition between isomerization, dehydrogenation, and -scission is severe. For medium-pore zeolites, the isomerization remains constrained and is faster than -scission.…”
Section: Comparison With Liquid-phase Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is well accepted that in gas phase conditions at low degree of pore occupancy, longer hydrocarbon chains are adsorbed more selectively than their shorter homologues on most zeolites because of the larger interaction energy [3][4][5][6]. This results in the selective catalytic conversion of the longer chains from mixtures of short and long chains, which already demonstrates the link between adsorption and catalysis on microporous solids [7].…”
Section: Introductionmentioning
confidence: 90%
“…Recently, it was shown that in hydroconversion of alkane mixtures the molecular competitions in the liquid phase are very different from those in the vapor phase (83,84). The competitive hydroconversion of n-heptane and n-nonane in their mixture at vapor-and liquid-phase reaction conditions was studied on Pt loaded USY and HY zeolite catalysts.…”
Section: M Akhmedov and S H Al-khowaitermentioning
confidence: 99%